(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
Is there a right to scientific research? Is it somehow connected to bioethics? In international law, a right to benefit from scientific progress is acknowledged and promoted. Could it include also the right to actively participate to the scientific research, meaning a right to take part to the decision making process on research? This right could have a positive impact on equality and on the sharing of the benefits of research. It could also promote new research agendas.